What unions no longer do - Rosenfeld, Jake, 1978- (Harvard University Press, 2014)
What Unions No Longer Do shows in detail the consequences of labor's decline: curtailed advocacy for better working conditions, weakened support for immigrants' economic assimilation, and ineffectiveness in addressing wage stagnation among African-Americans. In short, unions are no longer instrumental in combating inequality in our economy and our politics, and the result is a sharp decline in the prospects of American workers and their families.